Extension experience – pregnant women's health care in remote mode and in the context of Covid-19 pandemic (Research, Society and Development, 2022)
The creation of this online community extension project is based on the idea of collaborating with mother-child care. Objective: to present an experience report of the activities developed in the extension project with pregnant women in the context of online physiotherapeutic care during the Covid-19 pandemic. Methods: this is the report of experiences derived from an extension project which belongs to a faculty of Physiotherapy from Rio Grande do Sul. Each attendance was composed of round table, therapeutic exercise and information leaflets. Results: Participated in this extension project 17 pregnant women from 18 to 37 years old. Pregnant women reported a sense of well-being, as well as, there were no adverse events. The experience was considered rewarding for the team. Conclusion: After this project’s conclusion, the graduation students experience was satisfactory and the strengthening of the extension activities as a social commitment.